Fabric evolution across a discontinuity between lower and upper crustal domains from field, microscopic, and anisotropy of magnetic susceptibility studies in central eastern Eritrea, NE Africa - Ghebreab, Woldai; Kontny, Agnes; Greiling, Reinhard O. (Tectonics, 2007)
In the Neoproterozoic East African Orogen (EAO) of Eritrea, lower to middle crustal high-grade metamorphic rocks are juxtaposed against low-grade upper crustal rocks along diffuse tectonic contact zones or discontinuities. In the central eastern part of Eritrea, such a tectonic zone is exposed as a low-angle shear zone separating two distinct high- and low-grade domains, the Ghedem and Bizen, respectively. Integrated field, microfabric, and anisotropy of magnetic susceptibility (AMS) studies show that this low-angle shear zone formed during late deformation, D2, with top-to-the-E/SE sense of motion. The hanging wall upper crustal volcanosedimentary schists are mainly paramagnetic and the footwall middle crustal mylonitized orthogneisses are mainly ferrimagnetic. Magnetic fabric studies revealed a good agreement between metamorphic/mylonitic and magnetic foliations (Kmin) and helped to explain fabric development in the shear zone. The magnetic lineations (Kmax) reflect stretching lineations where stretched mineral aggregates dominate fine-grained mylonitic matrices and intersection lineations where microstructural studies revealed two fabric elements. AMS directional plots indicate that the orientations of the magnetic lineation and of the pole to the magnetic foliation vary systematically across the shear zone. While Kmax axes form two broad maxima oriented approximately N-S and E-W, the Kmin axes change from subhorizontal, generally westward inclination in the west to moderate to steep inclination in the direction of tectonic movement to the east. Because there is a systematic change in inclination of Kmin for individual samples, all samples together form a fairly well defined cluster distribution. The distribution of Kmin in combination with the E-W scattered plot of the Kmax is in accordance with the E/SE flow of mylonites over exhumed Damas core complex in the late Neoproterozoic. During the Cenozoic, the Red Sea rift-related detachments exploited the late orogenic shear zone, indicating that the discontinuities between ductile middle and brittle upper crustal layers in the region are reactivated low-angle shear zones and possible sites of core complexes.
Gesehen am 10.09.2019